Neon 1975-1985. - Vandevivere, Ignace; Galerie Neon, Brussel (Brussel : Galerie Neon, 1986)
François, Bernard ; Souply, Emile ; Warrand, Marcel ; Palisse, Jean-Claude ; Benon, Jean-Pierre ; Octave, MMC ; Bertrand, Veronique ; etc.
Nederlands & Frans & Engels
boek